2021
DOI: 10.24275/rmiq/bio2034
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of a thermostable extracellular esterase from Aspergillus niger

Abstract: Modelado de la biodegradación en biorreactores de lodos de hidrocarburos totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
(54 reference statements)
0
5
0
Order By: Relevance
“… 72 Reduced enzyme activity and stability reflects that histidine and serine may play a role in the enzyme's catalytic activity and substrate binding. Hamid et al 59 also reported the reduction in enzyme activity in the presence of SDS. Effect of organic solvents on enzyme's stability and activity was also determined in order for its utilization in industrial applications.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“… 72 Reduced enzyme activity and stability reflects that histidine and serine may play a role in the enzyme's catalytic activity and substrate binding. Hamid et al 59 also reported the reduction in enzyme activity in the presence of SDS. Effect of organic solvents on enzyme's stability and activity was also determined in order for its utilization in industrial applications.…”
Section: Discussionmentioning
confidence: 92%
“…Various reports are present on the determination of thermostability of esterase enzyme from various microorganisms. Hamid et al 59 reported an esterase enzyme from Aspergillus niger with 56% activity at 80 °C after 4 h of incubation. While Tang et al 60 studied a glucuronoyl esterase from Thielavia terrestris and reported its thermostability at 55 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ is reported to play important role in the structure and function of industrial enzymes (Haki & Rakshit, 2003). In previous studies, Ca 2+ stimulated lipases are reported for utilization in various industrial (Cherif et al, 2013; Hamid et al, 2021; Hertadi & Widhyastuti, 2015; Sayari et al, 2001). The addition of EDTA resulted in decrease of enzyme activity in this study and this confirms the fact that lipase is a metalloenzyme because EDTA is a strong inhibitor of metal dependent enzymes.…”
Section: Discussionmentioning
confidence: 97%
“…To evaluate the gene expression and molecular mass determination, SDS‐PAGE was used (Figure 2). Many reports are present on the use of SDS‐PAGE to measure the molecular mass of recombinant proteins (Basit et al, 2021; Gao et al, 2022; Hamid et al, 2021; Shariati et al, 2021; Zafar et al, 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrolases degrade polysaccharides of different lignocellulosic materials. Aspergillus species are the primary producers of several hydrolases, including esterases (Hamid et al, 2021), but they also produce enzymes that degrade lignin (Brink et al, 2019). The quantity and type of enzymes produced by fungi depend on the chemical composition of the material that they degrade (Costa et al, 2018, Martínez et al, 2017.…”
Section: Introductionmentioning
confidence: 99%